49.2k views
0 votes
Factorise2rs-4rt-6t+3s

User Mdlc
by
5.9k points

1 Answer

5 votes

Given expression:


2rs\text{ - 4rt - 6t + 3s}

Collect like terms:


=\text{ 2rs - 4rt - 6t + 3s}

Next, we bring the common terms:


=\text{ 2r(s - 2t) -3(2t - s)}

Re-writing the expression:


=\text{ -2r(2t - s) -3(2t -s)}

Since we have a common term on either side of the negative sign, we can write:


=\text{ (-2r -3)(2t-s)}

Answer:


=\text{ (-2r-3)(2t -s)}

Let us verify the answer:


\begin{gathered} (-2r\text{ -3)(2t-s)} \\ =-2r(2t\text{ -s) -3(2t -s)} \\ =\text{ -4rt + 2rs -6t + 3s} \end{gathered}

User Madamadam
by
5.3k points